How does reducing the dimension of feature vectors impact Biometric Systems that use Homomorphic Encryption? - Purim, Andreis G. M. (Anais do Simpósio Brasileiro de Cibersegurança (SBSeg); 2025: Anais do XXV Simpósio Brasileiro de Cibersegurança, 2025)
Homomorphic Encryption enables biometric systems to perform matching directly on encrypted feature vectors, preserving user privacy throughout the process. However, the high computational cost of encrypted-domain operations, especially on high-dimensional inputs, remain a major barrier to real-world use. This study presents a concrete example of how reducing the dimensionality of biometric feature vectors affects both matching accuracy and runtime, and discusses how system designers could estimate the trade-off between time savings and accuracy loss when choosing a target dimension. The code is available on Github.